2004
DOI: 10.1002/ccd.20024
|View full text |Cite
|
Sign up to set email alerts
|

Myonecrosis following stent placement: Association between impaired TIMI myocardial perfusion grade and MRI visualization of microinfarction

Abstract: Contrast-enhanced cardiac MRI (ceMRI) and TIMI myocardial perfusion grade analysis (TMPG) are proven methods for visualization of microinfarction and assessment of microvascular perfusion, respectively. To determine whether microvascular obstruction accounts for procedure-related myonecrosis, 14 poststent patients, 9 with procedural CK-MB elevation and 5 controls, underwent ceMRI and TMPG. All had TIMI 3 flow pre- and poststent. TMPG was normal in 12/14 pre- and 7/14 poststent. Those with poststent decline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…Recently, MRI visualization of microinfarction has been linked with impaired TMPG in 14 patients. 3 Our evaluation of the TMPG confirms these previous results but is further validated by consistency with 2 other techniques (CMR and IVUS) and extends these results to a larger sample undergoing elective PCI.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, MRI visualization of microinfarction has been linked with impaired TMPG in 14 patients. 3 Our evaluation of the TMPG confirms these previous results but is further validated by consistency with 2 other techniques (CMR and IVUS) and extends these results to a larger sample undergoing elective PCI.…”
Section: Discussionsupporting
confidence: 86%
“…2,3 Despite a variety of techniques to minimize compromise of side branches during stenting, 4 smaller vessels cannot always be protected, and some compromise of flow down branch vessels may be inevitable when long coronary stents are placed over areas of extensive atheroma. 5 Downstream embolization of material from the atheromatous plaque during stent implantation may be ubiquitous, 6 but the clinical relevance of embolization in native coronary arteries has been debated, particularly since the disappointing results from studies using distal protection devices in the setting of acute myocardial infarction.…”
Section: Editorial P 620 Clinical Perspective P 669mentioning
confidence: 99%
“…We and others have recently demonstrated that areas of new myonecrosis visualized with DE-MRI are linked to impaired TIMI perfusion grade on angiographic analysis immediately after the procedure. 14,25 In the present study, we have extended this by finding that areas of myocardium injured during PCI exhibit reduced myocardial perfusion for at least 24 hours after the interventional procedure.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, coronary stenting may also cause microvascular obstruction due to embolization. 19 Another well recognized cause of periprocedural MI is the compromise of large sidebranches …”
Section: Periprocedural MI and Sidebranch Occlusion With Coronary Stentsmentioning
confidence: 99%